Technologies for enhancing value addition, quality and safety of milk produced by smallholder farmers in Africa - Kurwijila, Lusato R.; Lore, Tezira A.; Omore, Amos O. (International Livestock Research Institute, 2005)
FAO 2003 data indicate that Africa imported over 5.6 million tonnes liquid milk equivalent worth about US$ 1.8 billion or 29% of the world dairy import trade. Part of this demand-supply gap for value added dairy products could be filled by processed dairy products from within the African region. While Africa produces about 28.7 million tonnes of milk annually (26.7 kg/per capita), in most countries more than 85% is sold as raw milk thus raising quality and food safety concerns. The paper reviews and discusses technologies that have been developed to address these problems including improvement of milk handling by informal milk traders, traditional fermentations, butter and cheese processing, milk preservation using lactoperoxidase (LPS) and in-pouch pasteurisation of liquid milk. It is concluded that Africa's dairy industry needs to grow from an industry dominated by informal actors to small and medium enterprises answering the needs of the changing socio-economic landscape of African countries.